How much is enough? Optimizing beehive stocking densities to maximize the production of a pollinator-dependent crop - Ramírez Mejía, Andrés F. (2024)
Animal pollination is essential to guarantee the economic viability of pollination-dependent crops, and honeybees (Apis mellifera L.) play a central role as the most used species worldwide for pollination service management. Despite its importance, recommendations on honeybee hive stocking density are based on rules of thumb that assume hives as standardized units and do not consider the contingencies of the crop's pollen deposition demand. We developed a mechanistic simulation model to assess the consequences of variant hive quality and stocking density scenarios for blueberry productivity per hectare. To do so, we used Bayesian models, field experiments and secondary information to parametrize the simulation and estimate flower visitation rate, pollen deposition, and fruit production at the crop level. We found that maximizing pollen deposition at the crop level can be achieved with seven high quality-hives ha−1 (20000 bees colony−1), whereas reaching similar levels of pollination with conventional hives (10000 bees colony−1) would require 20 hives ha−1. Also, optimal hive stocking densities to maximize blueberry yield ha−1 needs four high quality-hives ha−1, whilst similar levels of productivity could be reached with 20 conventional colonies ha−1. From an economic and productive perspective, a lower unit rental price for conventional hives compensates for the use of less, but more expensive, high quality hives. Therefore, deciding using either low or high-quality hives should be based on, for instance, the logistic implications of using ∼2.5 more hives ha−1 and the consequences of using colonies with a poorer sanitation state for pollination service stability. Our work set the basis for a more biological and evidence-based protocol for honeybee hive management in blueberry crops. Indeed, integrating honeybee and blueberry pollination ecology, we provide a pragmatic approach to maximize crop productivity based on the minimum beehive stocking densities that optimize pollen deposition and crop yield ha−1 depending on hive's quality. Knowing such a minimum allows for reduced operation costs for farmers, lower uncertainty of pollinators contribution to crop productivity and the risk of undesirable pollination scenarios, and helps to limit the potential negative impacts of saturating ecosystems with honeybees.